Using ChatGPT in Teaching Arabic as a Foreign Language - Nasaruddin, Nasaruddin (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study aimed to identify the educational needs that Arabic language teachers could fulfill using ChatGPT and the practical steps that Arabic language teachers could take to obtain responses from ChatGPT in accordance with their educational needs. This research examined the use of the ChatGPT platform in teaching Arabic to non-native speakers. This research used a descriptive method to present views and theories about Arabic language teaching using ChatGPT and how they could be applied in teaching Arabic as a foreign language. The results of this study indicated that Arabic language teachers could use ChatGPT to support their teaching by preparing rich, modern, and engaging educational materials in the form of texts, questions, and images. Through precise and directed commands, Arabic language teachers could obtain these materials from ChatGPT in a way that suited their educational needs, such as the topic of the lesson, types of texts, their quality and quantity, and the level of students benefiting from them. It is expected that the results of this research will benefit Arabic language teachers in utilizing ChatGPT to enhance their educational and professional levels.